2009
DOI: 10.1152/ajplung.90624.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate inhibits NF-κB function at multiple levels to limit airway smooth muscle cell cytokine secretion

Abstract: Seidel P, Merfort I, Hughes JM, Oliver BG, Tamm M, Roth M. Dimethylfumarate inhibits NF-B function at multiple levels to limit airway smooth muscle cell cytokine secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 48 publications
6
96
0
Order By: Relevance
“…Previous reports have suggested that, upon DMF treatment, phosphorylation of NFB transcription factors and subsequent nuclear translocation are attenuated (26,52). This occurs in an IKK/IB␣-independent manner and via other kinases, such as MSK-1, which phosphorylates p65 at Ser-468 (24,26,52). In agreement with these reports, we found that, in breast cancer cells, DMF reduces the nuclear content of phosphorylated and total p65 in an IKK/IB␣-independent manner.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous reports have suggested that, upon DMF treatment, phosphorylation of NFB transcription factors and subsequent nuclear translocation are attenuated (26,52). This occurs in an IKK/IB␣-independent manner and via other kinases, such as MSK-1, which phosphorylates p65 at Ser-468 (24,26,52). In agreement with these reports, we found that, in breast cancer cells, DMF reduces the nuclear content of phosphorylated and total p65 in an IKK/IB␣-independent manner.…”
Section: Discussionmentioning
confidence: 93%
“…Besides NFB inhibition, DMF has also been proposed to activate Nrf2 (23)(24)(25)(26). Indeed, we found that DMF significantly up-regulates the Nrf2 target gene, heme oxygenase 1 (HMOX1) mRNA, both in 2D and in MS (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GTCpFE is an effective NFĸB inhibitor, whereas ASA itself is not, even at much higher concentrations. The fumarate moiety has anti-inflammatory properties as shown by its ability to inhibit NFĸB signaling in a variety of cell lines and tissues 14,[25][26][27][28][29] . The prodrug strategy described herein, is amendable to other malignancies where multiple inflammatory pathways are active and contribute to the pathology.…”
Section: Discussionmentioning
confidence: 99%